Study of the rare decay J/ψ → μ+μ−μ+μ− - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2024)
The rare electromagnetic J/ψ → μ+μ−μ+μ− decay is observed with a significance greatly exceeding the discovery threshold, using proton-proton collision data collected by the LHCb experiment during 2016-2018 at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 5.4 fb−1. The rate of this decay is measured relative to that of the J/ψ → μ+μ− mode. Using the QED model for the four-muon decay in the efficiency estimation, its branching fraction is determined to beBJ/ψ→μ+μ−μ+μ−=1.13±0.10±0.05±0.01×10−6, where the uncertainties are statistical, systematic and due to the uncertainty on the branching fraction of the J/ψ → μ+μ− decay.